Project Based Learning: An Experience in the Area of Citizen Training - Barquero Ruiz, Alejandra (2020)
This article aims to share the experience developed with the project-based learning methodology (ABP) in the Civic Education II course (second semester of 2019). The course corresponds to the fourth year of the Baccalaureate in the Teaching of Social Studies and Civic Education, School of History of the National University of Costa Rica. The method used for the systematization of experience is called reflexivity and the construction of human experience. In the article theoretical and methodological foundations are exposed, a critical interpretation of the experience is made and concludes with the lessons learned.